2007
DOI: 10.1517/14656566.8.5.633
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoeconomics of the management of acute exacerbations of chronic obstructive pulmonary disease

Abstract: Acute exacerbations of chronic obstructive pulmonary disease (COPD) impose a significant burden on society in terms of morbidity, mortality, reduced quality of life and healthcare expenditure. New generations of antibiotics are used to treat exacerbations, and other modes of delivery involving home support are being implemented. The optimal strategy to manage exacerbations on pharmacoeconomic grounds depends on issues such as diagnosis of an exacerbation and safety, effectiveness and costs of available alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
0
7
0
2
Order By: Relevance
“…The likelihood of reductions in both costs and exacerbations is greater for older patients, although the cost per avoided severe exacerbation may still be high. Yet when one considers unmeasured consequences of repeated exacerbations (i.e., decreased quality of life, productivity loss, or caregiver time), the additional expenses may be compensated by additional benefits (D'Souza et al 2006; Simoens and Decramer 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The likelihood of reductions in both costs and exacerbations is greater for older patients, although the cost per avoided severe exacerbation may still be high. Yet when one considers unmeasured consequences of repeated exacerbations (i.e., decreased quality of life, productivity loss, or caregiver time), the additional expenses may be compensated by additional benefits (D'Souza et al 2006; Simoens and Decramer 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, multidimensional scores have been introduced in order to better assess COPD outcomes, particularly the mortality risk, even if results were variable due to their different specificity and sensitivity [3,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23]. The vast majority of studies have stated that exacerbations represent the main driver of COPD burden because they can affect morbidity, quality of life, hospitalizations, mortality, and related healthcare expenditure [24,25,26,27,28].…”
Section: Cost Trends In Real Lifementioning
confidence: 99%
“…The authors compared comparative costs and the comparative effectiveness of first-generation antibiotics (aminopenicillins, macrolides and tetracyclines) and second-generation antibiotics (eg, fluoroquinolones). Fluoroquinolones generally had higher acquisition costs than first-generation antibiotics, but both macrolides and fluoroquinolones were equally effective 12 13. In total, 38.8% of antibiotics were more effective and less costly than the comparator; 45.9% of antibiotics improved effectiveness but also increased costs; 15.3% of antibiotics were less effective and more costly than the comparator.…”
Section: Discussionmentioning
confidence: 98%
“…A study by Simoens and Decramer12 revealed that the cost of antimicrobials in an institution, especially in the intensive care unit, represents 30–50% of total drug costs and at least 50% of patients make use of antibiotics on hospitalisation. Hospitalisation costs accounted for more than 45% of healthcare costs and drug costs made up between 6% and 21% of costs.…”
Section: Discussionmentioning
confidence: 99%